Deposition Silver Based Thin Film on Stainless Steel 316l as Antimicrobial Agent Using Electrophoretic Deposition Method - Purniawan, Agung; Noerochim, Lukman; Widagdo, Laurentius Aditya; Sinaga, Ditta Gabriella (IPTEK The Journal for Technology and Science, 2023)
SUS316L stainless steel has been widely used in medical applications. However, some germs frequently adhere to the device surface, resulting in infections following implantation surgery. Unfortunately, the material lacks antibacterial characteristics that prevent microorganisms from adhering to the surface. This study aims to use electrophoretic deposition to deposit chitosan/silver (Ag) as an antibacterial agent on stainless steel 316L. The antimicrobial effects of chitosan and silver are well established. During the deposition, the rectifier voltage was adjusted to a constant 10 volts with a suspension pH range of 2.7 to 5.1. The effect of varying the pH of the suspension on the physical, mechanical, and antibacterial properties of chitosan/Ag thin films was investigated. The materials’ structure and morphology were studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier- transform infrared spectroscopy (FTIR). The antimicrobial inhibition was examined using the Kirby-Bauer antimicrobial test. The results reveal that increasing the pH of the suspension causes an increase in the thickness, size, and aggregation of the chitosan/Ag thin film. The highest thickness achieved during deposition with a pH 5.1 suspension is 5.265 ?m. The best antibacterial agent is achieved at a pH 3.5 suspension sample with an inhibitory zone diameter of 4 mm